5n-(2n-9)=27

Simple and best practice solution for 5n-(2n-9)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-(2n-9)=27 equation:


Simplifying
5n + -1(2n + -9) = 27

Reorder the terms:
5n + -1(-9 + 2n) = 27
5n + (-9 * -1 + 2n * -1) = 27
5n + (9 + -2n) = 27

Reorder the terms:
9 + 5n + -2n = 27

Combine like terms: 5n + -2n = 3n
9 + 3n = 27

Solving
9 + 3n = 27

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 3n = 27 + -9

Combine like terms: 9 + -9 = 0
0 + 3n = 27 + -9
3n = 27 + -9

Combine like terms: 27 + -9 = 18
3n = 18

Divide each side by '3'.
n = 6

Simplifying
n = 6

See similar equations:

| 5+2y/5 | | 8x-5x=3 | | 2/3*x=0 | | 14w-16w=10 | | 74b+47=29 | | 7x-4=-36+3x | | 9y+8x=72 | | 15u^2-20u/5u^2-40u=0 | | 15u^2-20u/5u^2-40u | | 4t-19=-19+7t | | 9=3x/5 | | 8n^2+18n+9=0 | | 8n^2+18n+9=o | | 3(4x+1)=3(3+3) | | (a/3)-5=6 | | 35(12+x)=945 | | 18w-10-16w=50 | | 3x+9+75=60 | | 6(2x-5)=3(2x-2) | | x/29=82 | | -2/5x=3+1 | | 2(10+x)=40 | | 3x+9+60=75 | | 3(7x-5)+5=10x-5 | | 8c^2+21c+10=0 | | 0=x^2+11+28 | | 116=2[(w+4)+w] | | 3x+6=60 | | -4/3(2x+1)=x-2 | | -48x^5=6x^3 | | .25*n=18 | | x+65=60 |

Equations solver categories